2004
DOI: 10.1093/annonc/mdh047
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and pharmacokinetics of palonosetron in patients receiving highly emetogenic cisplatin-based chemotherapy:a dose-ranging clinical study

Abstract: Palonosetron is an effective and well-tolerated agent for the prevention of CINV following highly emetogenic chemotherapy, with 3 and 10 microg/kg identified as the lowest effective palonosetron doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
113
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 20 publications
7
113
2
2
Order By: Relevance
“…The results of a Phase II study investigating the efficacy of single doses of palonosetron 0.3-90 g/kg IV have suggested that the agent does not demonstrate a marked dose-response effect on control of emesis in patients receiving cisplatin-based chemotherapy. 73 A complete response (no emesis, no retching, no rescue therapy) was achieved in 24%, 46%, 40%, 50%, and 46% of patients who received IV palonosetron at doses of 0.3-1.0 g/kg, 3.0 g/kg, 10.0 g/kg, 30.0 g/kg, and 90.0 g/kg, respectively. No significant differences in efficacy were observed between doses of 3 g/kg and 90 g/kg, although all of these doses showed a trend toward superiority compared with the lowest dose (0.3-1.0 g/kg).…”
Section: Palonosetronmentioning
confidence: 94%
“…The results of a Phase II study investigating the efficacy of single doses of palonosetron 0.3-90 g/kg IV have suggested that the agent does not demonstrate a marked dose-response effect on control of emesis in patients receiving cisplatin-based chemotherapy. 73 A complete response (no emesis, no retching, no rescue therapy) was achieved in 24%, 46%, 40%, 50%, and 46% of patients who received IV palonosetron at doses of 0.3-1.0 g/kg, 3.0 g/kg, 10.0 g/kg, 30.0 g/kg, and 90.0 g/kg, respectively. No significant differences in efficacy were observed between doses of 3 g/kg and 90 g/kg, although all of these doses showed a trend toward superiority compared with the lowest dose (0.3-1.0 g/kg).…”
Section: Palonosetronmentioning
confidence: 94%
“…Two doses were identified for Phase III investigation. 11 The objective of the current Phase III trial was to evaluate the efficacy and safety of single, fixed, intravenous (i.v.) doses of palonosetron 0.25 mg and 0.75 mg compared with a single i.v.…”
mentioning
confidence: 99%
“…A Phase II study showed that palonosetron maintains efficacy in preventing CINV for some days after highly emetogenic chemotherapy. 11 The 5-HT 3 receptor binding affinity of palonosetron is approximately 100-fold greater than others in its class, making it more potent than other receptor antagonists (pKi 10.45 for palonosetron vs. 7.6 for dolasetron, 8.39 for ondansetron, and 8.91 for granisetron). 10,13 In addition, the extended plasma elimination half-life of palonosetron (approximately 40 hours) 14 is substantially longer than first-generation agents (dolasetron, 7.5 hours; ondansetron, 4.0 hours; and granisetron, 8.9 hours).…”
mentioning
confidence: 99%
“…A dose-ranging study of palonosetron in patients receiving chemotherapy of high emetic risk (97% received cisplatin) tested intravenous doses from 0.0003 to 0.09 mg/kg and identified 0.003 and 0.0.01 mg/kg as the lowest effective palonosetron doses [11]. Three subsequent randomized trials compared a 0.25-mg fixed palonosetron dose, a 0.75-mg fixed palonosetron dose, and a standard comparator of either intravenous ondansetron 32 mg [1,13] or intravenous dolasetron 100 mg [10].…”
Section: Dose Of 5-ht 3 Receptor Antagonistsmentioning
confidence: 99%